Metal concentrations in soil, soil solution, grass, earth worm and batch tests (ISO 11268-2) from a field trial with contaminated soil, biochar and peat - Tiberg, Charlotta; Kleja, Dan; Sjöstedt, Carin; Fröberg, Mats; Rijk, Ingrid; Dahlin, Sigrun; Larsson, Maria; Ekblad, Alf; Sjöberg, Viktor; Enell, Anja (Swedish Geotechnical Institute, 2025)
The dataset contains data from a field trial in which soil contaminated with metals and PAHs was stabilised with biochar and peat. The aim was to reduce the solubility and availability of the contaminants while improving soil quality. The trial and analyses are described in more detail in an open access publication in Environments: https://doi.org/10.3390/environments12110447
The data reported here are concentrations of metals, other elements, organic carbon, pH and CEC in soil; concentrations of metals, other elemetns and dissolved organic carbon as well as pH in the soil solution and eluate from leaching tests (batch tests); metal concentrations in grass (Lolium Perenne) and earthworms (Eisenia fetida).

Datasetet innehåller data från ett fältförsök där jord förorenad med metaller och PAH stabiliserats med biokol och torv. Syftet var att minska lösligheten och tillgängligheten av föroreningarna och samtidigt förbättra markkvaliteten. Försöket och analyserna beskrivs närmare i open access publikation i tidskriften Environments: https://doi.org/10.3390/environments12110447
De data som redovisas är koncentrationer av metaller, andra grundämnen och organiskt kol samt pH och CEC i jord; koncentrationer av metaller, andra grundämnen och löst organiskt kol samt pH i marklösningen och i eluat från lakförsök (skakförsök); metallhalter i gräs och mask.
Metallkoncentrationer i jord, porvatten, gräs, daggmask och skakförsök (ISO 11268-2) från ett fältförsök med förorenad jord, biokol och torv
Keywords: SOIL CHEMISTRY; soil leaching; urlakning av mark; chromium; krom; contaminated soil; förorenad mark; copper; koppar; earthworm; daggmask; field experiment; fältförsök; lead; bly; mercury; kvicksilver; metal; metaller; arsenic; arsenik; peat; torv; barium; barium; zinc; zink; Poaceae; gräsväxter; Lumbricidae; daggmaskar; soil solution; markvatten; grass; gräs; lysimeter; lysimeter; biochar; biokol; leaching test; lakförsök; Environmental Sciences; Miljövetenskap